Motivasi Berpuasa Ramadhan dan Moralitas Remaja - Marlina, Elly (Jurnal Ilmu Dakwah, 2012)
This study aimed to determine the relationship between motivation of Ramadan fasting and morality in 120 students of the eighth grade of SMP Muhammadiyah 3 Bandung. The results showed that there is a positive and significant relationship between motivational variables of Ramadan fasting with the teens morality so it can be said that the higher motivation of Ramadan fasting, the higher the adolescent morality, and conversely, the lower the motivation of Ramadan fasting, the lower the their morality. Effective contribution given Ramadan fasting motivation variable related to their morality is around 29.8%, while the remaining 70.2% were contributed by other factors that influence their morality are the home, school neighborhood, peers, religious terms and leisure activities.